Odpowiedzi

Najlepsza Odpowiedź!
2009-11-02T21:18:02+01:00
Aby wyznaczyć punkty wspólne porównujemy 2 wyrażenia:

a) w(x)=⅓x³+x+2 L:y=4x+2
⅓x³+x+2 = 4x+2
⅓x³-3x = 0
⅓x(x²-6) = 0 => x=0 (∧y = 2) ∨ x=√6(∧y= 4√6+2) ∨ x=-√6(∧ y=-4√6+2)
-> 3 pary punktów wspólnych

b)w(x)=4x³-x²-5x+3 l;y=3x+1
4x³-x²-5x+3 = 3x+1
4x³-x²-8x+2 = 0
(4x-1)(x²-2) = 0 => x=1/4 (∧y =7/4) ∨ x=√2(∧y= 3√2+1) ∨ x=-√2(∧ y=-3√2+1)

c)w(x)=x⁵-4x⁴+3x³+x² l;y=4x-3
x⁵-4x⁴+3x³+x² = 4x-3
x⁵-4x⁴+3x³+x²-4x+3 = 0
(x-1)(x+1)(x-3)(x²-x+1) = 0
=> x=1 (∧y =1) ∨ x=-1(∧y= -7) ∨ x=3(∧ y=9)
2 3 2
2009-11-02T22:34:54+01:00
Należy porównać obaa 2 wyrażenia:

a)
⅓x³+x+2 = 4x+2
⅓x³-3x = 0
⅓x(x²-6) = 0
x=0 v x=√6 v x=-√6

x=0
y = 2



x=√6
y= 4√6+2

x=-√6
y=-4√6+2

b)w(x)=4x³-x²-5x+3 l;y=3x+1
4x³-x²-5x+3 = 3x+1
4x³-x²-8x+2 = 0
(4x-1)(x²-2) = 0
x=1/4 v x=√2 v x=-√2
trzy punkty
x=1/4
y =7/4



x=√2
y= 3√2+1



x=-√2
y=-3√2+1

c)
x⁵-4x⁴+3x³+x² = 4x-3
x⁵-4x⁴+3x³+x²-4x+3 = 0
(x-1)(x+1)(x-3)(x²-x+1) = 0
x=1vx=-1 x=3 Δ<0

x=1
y =1


x=-1
y= -7


x=3
y=9
2 5 2